Investigation of Hospitality and Business School English Instructors' TPACK in the Online Learning Contex - Ni Komang Punia Antari; Made Hery Santosa; Putu Tika Virginiya (Journey: Journal of English Language and Pedagogy, 2023)
The rapid growth of technology affects every aspect of our life, including education, and its use has become an essential part of the instructional process. This study aimed to investigate how TPACK is developed and applied throughout the instructional process of 12 English instructors in a Hospitality and Business School in Bali and what challenges are faced in integrating technology into their online learning context. Using a mixed-methods research design, the study utilized two instruments: a survey and an open-ended interview. Prior to data collection, instruments were evidenced to be valid and reliable (α=.98). The result shows that the TPACK of English teachers at the Hospitality and Business School was categorized as "good". This means that the instructors have developed and applied their TPACK competency well in all domains including TK, CK, PK, PCK, TCK, TPK, TPACK with the mean 4.4. The interview revealed three main challenges in integrating technology into their class: individual psychology, technical issues, and students' technology literacy. Policymakers should consider preparing instructors' TPACK in the vocational context be ready to cope with the limitations of an online learning environment with professional development activitie